Increasing Self Acceptance of Coping Strategies In People With HIV/AIDS (ODHA) - Virda, Enny; Dedy Setiawan, Ghufron; Dianova, Vivi Uma; Windartik, Emyk (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The existence of discrimination and stigma made HIV/AIDS patients choose to avoid social environment, tend to isolated themselves and more often to be alone so that patients have not been able to accepted themselves with the latest status as HIV/AIDS patients. Low acceptance made PLWHA experience failure interacted with people and the environtment so that coping strategies are needed to solve problems. This study aims to prove the relationship of coping strategies with self-acceptance in HIV/AIDS patients in the working area of the Sooko Mojokerto Health Center. This study used a correlational analytic design through a cross sectional approach obtained a sample of 42 people involved in research selected used purposive sampling technique. Data collection used the WOCQ questionnaire to measure coping strategies and IIQ to measure self acceptance. The results of this study were tested used Spearmen rho and obtained a p-value of 0.000 with α = <0.05, which means that there is a relationship between coping strategies and self acceptance in HIV/AIDS patients in the working area of the Sooko Mojokerto Health Center. The importance of choosing the right coping strategy is problem focused coping in HIV/AIDS patients can help patients in increasing self-acceptance in themselves because HIV/AIDS patients have their own efforts in terms of solving problems.